Designing an Integrated Website for Telukawur Marine Tourism Village, Jepara Regency: A Platform for Information Dissemination, Tourism Promotion, and Digital Branding - Syuhada Khairunnisa; R. Bambang Aditya Nugraha; Atikah Nurhayati; Lintang Permata Sari Yuliadi; Asep Agus Handaka Suryana; Fanny Kristiadhi (Jurnal Pariwisata Nusantara (JUWITA), 2026)
Purpose: This study aims to develop an integrated tourism website for Telukawur Marine Tourism Village, Jepara Regency, Indonesia, by identifying its tourism potential based on the 5A tourism framework. The website is designed to serve as a platform for information dissemination, tourism promotion, and digital branding. Method: This study adopted a mixed methods approach using the User-Centered Design (UCD) framework. Qualitative data were collected through semi-structured interviews with two key stakeholders, namely the village secretary and the chairperson of the Village Owned Enterprise (BUMDes). Quantitative data were collected by distributing questionnaires to 61 tourists and potential tourists aged 18–40 years who were familiar with internet use and had experience or interest in marine ecotourism. The questionnaires were used to evaluate the website using a website evaluation questionnaire and the System Usability Scale (SUS). Result: The findings identified tourism potential across the five dimensions of the 5A tourism framework, namely attractions, accessibility, amenities, accommodation, and ancillary services. The research instrument was confirmed to be valid (r > 0.361) and reliable (Cronbach's Alpha = 0.917). The website evaluation achieved an overall score of 90.91%, which was categorized as Very Good, while the SUS evaluation produced an average score of 82.21, indicating an Excellent level of usability with an Acceptable level of acceptability. Contribution: This study proposes a validated model for developing an integrated tourism website that combines information dissemination, tourism promotion, and digital branding within a single digital platform. The proposed model addresses the limited research on digital tourism development in small-scale coastal tourism villages and provides a practical reference for other marine tourism villages participating in the Dewi Bahari Program of the Ministry of Marine Affairs and Fisheries of the Republic of Indonesia.